Motivational Teaching Strategies to Foster Oral Production Skill (2024)
ABSTRACT: This action research project intended to explore the impact of implementing motivational teaching strategies to foster oral production skills in foreign language learners of eighth grade in a public school in Medellín, Colombia. To collect data, the instruments used were a research journal, two questionnaires which were conducted at the beginning and at the end of the implementation of the project, self-assessment, oral presentations and voice recordings, an external observation, and an interview with the cooperating teacher. Data analysis revealed that the implementation of motivational teaching strategies helped to promote students' commitment and responsibility to their learning process. This also helped students to improve their oral production skills and participation in the classroom. While these improvements are significant for students and the strategies were successful, it is important to develop them in a context where the time is more suitable for the implementation of the strategies and the creation of study routines.